(untitled) (Medicine Today, 2021)
Introduction: The year 2019 will be remembered in the human history by the mark of an unknown diseases plaguing the whole world with its devastation, namely coronavirus disease 2019 (COVID-19). This pandemic caused by a novel strain of RNA virus has caused a catastrophic health outcome for millions of world citizens but in many cases only the physical aspect of the disease came under consideration. Materials & Methods: This review is based on ample literature search of Medline, the Cochrane Database of Systemic Reviews, and citation lists of relevant publications. Discussion: COVID-19 pandemic has caused a variety of health problems including mental health issues. Initial panic about the completely unknown (Novel) virus plaguing the world was soon joined by an array of mental health problems like anxiety, depression, combined anxiety and depression, traumatic stress etc. Amidst the chaos of unpredictability, mortality, overstretched health facilities etc. we often downplay the importance of paying attention to the mental side of the disease spectrum. As a result, outcomes like child abuse, domestic violence and suicide can increase. Conclusion: It is of utmost importance to educate mass people about the coping strategies to go through this hard time, to ensure proper news sharing, to screen people who are at risk of developing mental health problems and to provide support to those who are in need. Local and International consensus guideline should be planned to deal with this issue. Medicine Today 2021 Vol.33(2): 169-171